Synthesis of Unnatural Diethyl 2-Hydroxysuccinate From 2,3-Dihydroxysuccinic Acid As a Starting Material for Annonine Building Blocks - Shneine, Jewad K (Al-Nahrain Journal of Science, 2018)
Since Annonin I is considered as a biological active natural product, this work concerns on the synthesis of the side chain of this biologically important molecule as a part of total synthesis of the whole molecule. As a result of our retrosynthetic analytical method, the commercial available 2,3-Dihydroxysuccinic acid A and pentyl halide B represent generally the main building blocks for the synthesis. The synthesis begins with Fischer esterification of the dicarboxylic acid 1 and then conversion into Diethyl 3-bromo-2-hydroxysuccinate 3 which was the key compound to obtain the acetal (2-phenyl-1,3-dioxan-4-yl) methanol 6. In this respect, two different synthetic routs were evaluated to transform compound 3 into 6. Furthermore, the removal of bromide step (reduction of 3) was also studied using different reducing agents.